The necropolis of the Casa Romana do Castro de São Domingos (Lousada, Portugal): a funerary space from the Early Middle Ages - Paulo André Pinho Lemos; Manuel Nunes; Bruno M. Magalhães (Antropologia Portuguesa)
Between 2017 and 2021 seventeen graves were identified in the context of the research project ‘Excavation, study, and musealization of the Casa Romana do Castro de São Domingos’ (Lousada, Portugal). Human bones were absent in all the fourteen graves excavated, most likely due to the acidity of the granitic soil, although the tombs length had shown that at least two were built for the burial of non-adult individuals. Only a bronze buckle was recovered as a grave good which may be related to the violation of most of the tombs, but mainly to the presence of a community with few economic resources. The funerary architecture showed three different types of graves, showing a possible older and central area from where the burial ground grew. The proximity of roads is sometimes the main condition for the location of a burial ground and not necessarily the edification of a religious temple. The comparison with the funerary architecture of other Portuguese burial grounds shows that the cemetery of the Casa Romana do Castro de São Domingos may have been in use between the Late Antiquity and the High Middle Ages.